2020
DOI: 10.1007/s12182-019-00409-w
|View full text |Cite|
|
Sign up to set email alerts
|

Interactions of ferro-nanoparticles (hematite and magnetite) with reservoir sandstone: implications for surface adsorption and interfacial tension reduction

Abstract: There are a few studies on the use of ferro-nanofluids for enhanced oil recovery, despite their magnetic properties; hence, it is needed to study the adsorption of iron oxide (Fe 2 O 3 and Fe 3 O 4) nanoparticles (NPs) on rock surfaces. This is important as the colloidal transport of NPs through the reservoir is subject to particle adsorption on the rock surface. Molecular dynamics simulation was used to determine the interfacial energy (strength) and adsorption of Fe 2 O 3 and Fe 3 O 4 nanofluids infused in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 35 publications
0
19
0
Order By: Relevance
“…Hence, the suspended particles in a liquid will eventually undergo polarization, which can result in improving the trapped oil by improving the mobility ratio of the fluids due to the electrorheological effect that leads to the incremental stage of the viscosity of the nanofluids [49]. Various dielectric nanofluids activated by EM wave irradiation have been studied in the last decade and showed promising results for enhanced oil recovery [49,54,60,97,98].…”
Section: Nanoparticles For Em-assisted Eormentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, the suspended particles in a liquid will eventually undergo polarization, which can result in improving the trapped oil by improving the mobility ratio of the fluids due to the electrorheological effect that leads to the incremental stage of the viscosity of the nanofluids [49]. Various dielectric nanofluids activated by EM wave irradiation have been studied in the last decade and showed promising results for enhanced oil recovery [49,54,60,97,98].…”
Section: Nanoparticles For Em-assisted Eormentioning
confidence: 99%
“…Recently, Ali A.M. et al (2020) [98] investigated the adsorption behavior of the Ferronanofluids of Fe 2 O 3 and Fe 3 O 4 on oil recovery. Studying the role of the adsorption capacity of the nanoparticles is significant because the transport mobility of the nanofluids in a reservoir is largely attributed to the adsorption of the particles on the surface of the rock.…”
Section: Ferro-nanofluidsmentioning
confidence: 99%
“…Mirchi et al (2017) measured the equilibrium IFT and found the surfactant solution playing an important role in local trapping of oil phase during spontaneous imbibition. Ali et al (2020) proved ferro-nanoparticles accounted for the effectiveness in reducing interfacial tension because of higher silicate sorption capacity.…”
Section: Introductionmentioning
confidence: 97%
“…Therefore, magnetic nanoparticles are easily separated from the dispersion liquid by an external magnetic field and, thus, can be reused [ 37 , 38 ]. At present, research on nanomagnetic fluids in oil and gas production mainly focuses on reservoir fracture identification [ 39 ], oil-water front monitoring [ 40 ], and oil recovery improvement [ 41 , 42 , 43 , 44 ], while some scholars have carried out preliminary investigations of drag reduction by nanomagnetic fluids. Sun et al [ 45 ] designed a magnetic viscous fluid drag reduction device with a closed loop by placing a permanent magnet outside the tube wall.…”
Section: Introductionmentioning
confidence: 99%